Homocysteine Induces DNA Synthesis and Proliferation of Vascular Smooth Muscle Cells by a Hydrogen Peroxide-Independent Mechanism - KARTAL ÖZER, NESRİN (MARY ANN LIEBERT, INC, 1999)
Elevated plasma levels of homocysteine have been identified as an important and independent risk factor for cerebral, coronary, and peripheral atherosclerosis, although the mechanisms are unclear. Homocysteine has been shown to promote cell proliferation and induction of the gene transcription factor c-fos in vascular smooth muscle cells. Earlier reports have suggested that homocysteine exert its effect via hydrogen peroxide (H2O2) produced during its metabolism. To evaluate the contribution of homocysteine to the pathogenesis of vascular diseases, we examined whether the effect of homocysteine on vascular smooth muscle cell growth is mediated by H2O2. W e observed that 1.0 m M homocysteine induces DNA synthesis by 1.5-fold and proliferation of vascular smooth muscle cells two-fold in the presence of peroxide scavenging enzyme, catalase (2,600 U/ml). Our results suggest that homocysteine induces smooth muscle cell growth by an H2O2-independent pathway and that the effects of homocysteine may sum together with the known initiating events produced by oxidative stress and accelerate the progression of atherosclerosis. Antiox. Redox Signal. 1, 365-369.
Keywords: DISEASE; KINASE; RISK; HYPERHOMOCYSTEINEMIA; ARTERIOSCLEROSIS; GENERATION; ACTIVATION; INDUCTION; GROWTH; INJURY